Critical Race Theory, Race Equity, and Public Health: Toward Antiracism Praxis - Ford, Chandra L. (American Public Health Association, 2010)
Racial scholars argue that racism produces rates of morbidity, mortality, and overall well-being that vary depending on socially assigned race. Eliminating racism is therefore central to achieving health equity, but this requires new paradigms that are responsive to structural racism's contemporary influence on health, health inequities, and research. Critical Race Theory is an emerging transdisciplinary, race-equity methodology that originated in legal studies and is grounded in social justice. Critical Race Theory's tools for conducting research and practice are intended to elucidate contemporary racial phenomena, expand the vocabulary with which to discuss complex racial concepts, and challenge racial hierarchies. We introduce Critical Race Theory to the public health community, highlight key Critical Race Theory characteristics (race consciousness, emphases on contemporary societal dynamics and socially marginalized groups, and praxis between research and practice) and describe Critical Race Theory's contribution to a study on racism and HIV testing among African Americans.